Generalization of Conditioned Fear and Obsessive-Compulsive Traits - Kaczkurkin, Antonia N (2013)
Generalization of conditioned fear refers to the transfer of the conditioned fear response to stimuli that resemble the original conditioned stimulus. Overgeneralization of conditioned fear has been associated with panic disorder and generalized anxiety disorder and may be relevant to obsessive-compulsive (OC) symptoms as well. This study represents the first attempt to determine the degree to which individuals with high versus low OC traits over generalize conditioned fear. We hypothesized that the high OC individuals, particularly those characterized by overestimation of threat, would show overgeneralization of conditioned fear compared to controls as measured by behavioral and psychophysiological (fear-potentiated startle) measures. The results of this study show an interaction between the high and low Threat Estimation groups as measured by the Obsessive Beliefs Questionnaire, which suggests that those who have a tendency to overestimate threat show overgeneralization of conditioned fear. This finding suggests that the relation between OC symptoms and overgeneralization of conditioned fear may be specific to the high threat estimation component of OC symptoms.